Covalent organic framework-LZU1@PEI@Fe3O4-based magnetic dispersive micro-solid phase extraction of tetracyclines from environmental water prior to HPLC analysis. Issue 37 (3rd September 2021) - Zhang, Ying; Ning, Yuhan; Liao, Wanliang; Wang, Weiping; Wang, Ai-Jun
Abstract : Schematic of the m-μ-dSPE-HPLC strategy for the extraction and detection of TCs. Abstract : In this work, COF-LZU1@PEI@Fe3 O4 was synthesized by immobilization of COF-LZU1 onto the surface of polyethyleneimine-functionalized Fe3 O4 nanoparticles (PEI@Fe3 O4 ) and employed as an adsorbent for magnetic dispersive micro-solid phase extraction of tetracyclines (TCs). COF-LZU1@PEI@Fe3 O4 was characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction and nitrogen adsorption–desorption isotherms analysis. The optimal extraction and desorption conditions were as follows: 15.00 mL sample solution (pH 7.0) extracted with 5.0 mg of adsorbent for 30 min at 30 °C, and then desorbed with 1.50 mL methanol/acetonitrile/0.02 mol L −1 oxalic acid solution (v/v, 1 : 2 : 7). Good linearities were obtained between the peak area and TC concentration ranging from 5–500 μg L −1 with correlation coefficients ( R 2 ) higher than 0.9992 and limits of detection lower than 0.51 μg L −1 . The relative standard deviations (RSDs) of intra-day and inter-day were less than 5.7% and 7.4%, respectively. The developed method was successfully applied to the determination of TCs in environmental water samples with recoveries in the range of 87.0–113.8% and RSDs less than 5.1%, suggesting great potential of COF-LZU1@PEI@Fe3 O4 for efficient extraction and analysis of trace TCs in water samples.